IMPROVING STUDENTS' READING COMPREHENSION THROUGH TEAMS-GAMES-TOURNAMENTS (TGT) IN GRADE VIII STUDENTS OF SMP NEGERI 2 MAOSPATI - Nurdani Yulian Ahmad (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research aims to improve the reading comprehension of grade VIII students of SMP Negeri 2 Maospati through the application of the Teams-Games-Tournaments (TGT) learning model. The research uses the Classroom Action Research (PTK) method which is carried out in two cycles. The subjects of the study were 29 students of grade VIII. Data was collected through reading comprehension tests, observation of student activities, and documentation, then analyzed descriptively, quantitatively, and qualitatively. The results of the study showed that there was an increase in reading comprehension in each cycle. The initial average score was 63 with 28% completeness, increased to 72 with 56% completeness in the first cycle, and reached 81 with 88% completeness in the second cycle. This increase was influenced by the implementation of TGT measures involving group work, academic games, and tournaments, thereby creating active, fun, and competitive learning in a healthy manner. It can be concluded that the TGT model is effective in improving reading comprehension while encouraging student activity and motivation. Therefore, TGT can be used as an alternative to Indonesian learning strategies, especially to improve reading comprehension skills at the junior high school level.